Control of Single Stage Grid Tied Photovoltaic Inverter Using Incremental Conductance Method - K. Rajasekhara Reddy; V. Nagabhaskar Reddy; M. Vijaya Kumar (Institute of Advanced Engineering and Science, 2018)
In this investigation, a study on grid-connected Photovoltaic (PV) system with single stage power conversion (SSPC) is proposed. Double Stage Power Conversion (DSPC) topology contains two power conversion stages namely DC-DC conversion and DC-AC conversion, but the SSPC system converts DC power to high-quality AC power supply for grid connected PV system. The SSPC system has several advantages over DSPC, such as better use of the PV arrays, higher efficiency, low cost and compact size. Present work proposes a Sinusoidal Pulse Width Modulation (SPWM) along with incremental conductance Maximum Power Point Tracking (IC-MPPT) for inverter switching. The PV voltage and Grid Voltages verifies under normal and change of atmospheric conditions using MATLAB / SIMULINK.